2017
DOI: 10.3389/fendo.2017.00107
|View full text |Cite
|
Sign up to set email alerts
|

The Eight and a Half Year Journey of Undiagnosed AD: Gene Sequencing and Funding of Advanced Genetic Testing Has Led to Hope and New Beginnings

Abstract: BackgroundActivity-dependent neuroprotective protein (ADNP) is one of the most prevalent de novo mutated genes in syndromic autism spectrum disorders, driving a general interest in the gene and the syndrome.AimThe aim of this study was to provide a detailed developmental case study of ADNP p.Tyr719* mutation toward improvements in (1) diagnostic procedures, (2) phenotypic scope, and (3) interventions.MethodsLongitudinal clinical and parental reports.ResultsAD (currently 11-year-old) had several rare congenital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

8
2

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 51 publications
1
40
0
3
Order By: Relevance
“…The more we research the ADNP protein and gene, in a variety of ways including that of detailed descriptive case reports of patients with mutations of this gene (Gozes et al 1999;Magen and Gozes 2014;Gozes et al 2015a), the better we will gain a valuable understanding of this unique autistic syndrome. While some previous case reports followed ADNP child development (e.g., Gozes et al 2015aGozes et al , 2017a, this is the first longitudinal study evaluating the Vineland-II and the ABC questionnaires' results, paving the path to a better understanding of the disease natural history, toward rational clinical development.…”
Section: Resultsmentioning
confidence: 96%
“…The more we research the ADNP protein and gene, in a variety of ways including that of detailed descriptive case reports of patients with mutations of this gene (Gozes et al 1999;Magen and Gozes 2014;Gozes et al 2015a), the better we will gain a valuable understanding of this unique autistic syndrome. While some previous case reports followed ADNP child development (e.g., Gozes et al 2015aGozes et al , 2017a, this is the first longitudinal study evaluating the Vineland-II and the ABC questionnaires' results, paving the path to a better understanding of the disease natural history, toward rational clinical development.…”
Section: Resultsmentioning
confidence: 96%
“…Furthermore, premature primary tooth eruption was recently suggested as an early diagnostic biomarker for ADNP syndrome, with ADNP also regulating tooth eruption in mice (17,18). In-depth case studies of ADNP syndrome provide a broad view of the phenotype and identified, among other impairments, global developmental delays, ID, speech impediments, and motor dysfunctions (17,19,20). With more than 160 children diagnosed (http://www.adnpkids-researchfoundation.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, de novo, mostly truncating mutations in ADNP lead to cognitive impairments and autism in children [23][24][25][26]. Importantly, we have recently shown that serum ADNP content [27] is correlated with premorbid intelligence.…”
Section: Blood Biomarkersmentioning
confidence: 96%